ANALISIS BALANCED SCORECARD SEBAGAI ALAT UKUR PENILAIAN KINERJA PADA PT. XYZ - Hermin Nainggolan; Noura Adrianti (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2023)
This study aims to determine how the application of the balance scorecard as a measuring instrument for performance assessment at the PT. XYZ. Performance assessment analysis is carried out on 4 perspectives, namely: (1) financial perspective, (2) customer perspective, (3) internal business perspective, and (4) learning and growth perspective. Data collection techniques using questionnaires, documentation and literature study. The results of study showed that: (1) The financial perspective is measured by 3 instruments, namely the economic ratio is at the “economic” level, the efficiency ratio is at the “less efficient” level, and the effectiveness ratio is at the “very effective” level. (2) The customer perspective shows “very satisfied” at 90% and “satisfied” at 10%. (3) Internal business perspective is measured by 5 instruments, namely the Bed Occupancy Rate (BOR) is at the “ideal” level (69.48%), the Average Length of Stay (ALOS) is at the “ideal” level (6 days), Turn Internal Over (TOI) is at the “efficient” level (3 days), the Net Death Rate (NDR) is at the “ideal” level (22 people per 1,000 patients), and the Gross Death Rate (GDR) is at the “ideal” level ( 43 people per 1,000 patients). (4) The growth and learning perspective is measured by 2 indicators, namely the employee retention rate with a “good” score and the employee's training level with a “good” score.